InvestiGators. Ants in our P. A. N. T. S. - Green, John Patrick, 1975- (Green, John, 1975- InvestiGators (Series), 2021)
"With agent Brash trapped in a mysterious coma, the technicians at S.U.I.T. have designed the ultimate replacement: RoboBrash This high-tech replica has been programmed with all of the original Brash's crime-fighting skills and knowhow--but it seems he's got a few bugs in his system Will Mango and his new partner be enough to stop the giant ants that are on a rampage in the city?"--Provided by publisher.